Shape of the future - Dorling, D (Resurgence Trust, 2024)
Danny Dorling reviews The Next Supercontinent: Solving the Puzzle of a Future Pangea by Ross Mitchell. Why write a book about the possible future supercontinent dubbed Amasia, a landmass not expected to fully form until 200 million years from now? Author Ross Mitchell credits the naming to Paul Hoffman, a geologist currently based in Beijing at the Institute of Geology and Geophysics of the Chinese Academy of Sciences. What Mitchell’s work has mostly concerned until now is the past, constructing the record of what happened before. To get us interested in that, and why it matters, he has written instead about the future. But what this book is actually about is neither the future nor the past: The ...